B7-H7 Is Inducible on T Cells to Regulate Their Immune Response and Serves as a Marker for Exhaustion - Luu, Khang; Schwarz, Herbert; Lundqvist, Andreas (Frontiers in Immunology, 2021)
The discovery of immune checkpoints highlights the complexity of T cell signalling during an immune response. Upon activation, T cells express several molecules to regulate their function and to prevent overactivation. B7 homolog 7 (B7-H7) is expressed in tumours and associated with a worse prognosis. However, conflicting data regarding its function suggest that it can be both stimulatory and inhibitory. In this study we report that B7-H7 is also expressed on T cells upon cross-linking of CD3 and CD28 and that additional stimulation via CD137 further enhance the expression of B7-H7. B7-H7 is preferentially expressed on exhausted Th1 and Tc1 cells with an impaired secretion of TNF-α and IFN-γ. Blockade of B7-H7 with its natural receptor, recombinant CD28H, enhances T cell proliferation and activation. Thus, B7-H7 represents another target for immunotherapy and a biomarker to select for active effector T cells with relevance for adoptive cell transfer therapy.